Basic Okinawan From Conversation to Grammar - Shinzato, Rumiko (University of Hawai'i Press, 2023)
The first Okinawan language textbook written for English-speakers, Basic Okinawan: From Conversation to Grammar is a groundbreaking work that will help students develop conversational skills and build a solid foundational understanding of the language’s grammar and vocabulary. The lessons are geared for students learning in the classroom or on their own and do not assume knowledge of Japanese.The ten learner-centered units in Part I systematically and incrementally introduce grammar and vocabulary through the story of Niko, an American exchange student in Okinawa. Each unit offers authentic dialogues focused around cultural themes, followed by concise grammar and vocabulary explanations, ample exercises, and situation-based applications. Lessons conclude with cultural notes that advance the unit’s themes, linking language learning with a wide range of disciplines such as history, geography, literature, religion, and popular culture.